Dialogues between Scenic Light and the exercise of teaching (DAPesquisa, 2020)
The following article establishes dialogues between Scenic Light as a component language of the staging, with the exercise of teaching and the formation of theater teachers in graduation courses. We discuss two perspectives about the dialogue propoused, the first about the formation of teachers through the understanding of the concept of teacher-artist and the other about the processes of theater light designers formation in Brazil, considering theory and practice as inseparable territories.